1990
DOI: 10.1161/01.atv.10.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Thrombogenicity of vascular cells. Comparison between endothelial cells isolated from different sources and smooth muscle cells and fibroblasts.

Abstract: When the endothelial cell layer Is damaged, a thrombotic reaction starts on the cells' subendothelium and on the connective tissue deposited by smooth muscle cells in the deeper layers. When more severe vascular damage occurs, hemostasis will Involve the vessel adventitia In which fibroblasts are found. In this article, the influence of in vitro cultured endothelial cells, smooth muscle cells, and fibroblasts on the hemostatic balance was studied. To do so, perfusions were performed with low molecular weight h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 32 publications
(25 reference statements)
2
38
0
Order By: Relevance
“…Consistent with previous studies, 15,29 fibroblasts and SMCs supported 131-fold and 8.7-fold higher rates of factor Xa generation, respectively, than HUVECs (Table 3). Stimulating HUVECs for 4 hours with 1nM TNF␣ increased factor Xa generation 19.7-fold (Table 3).…”
Section: Fibrin Network Density Correlates With Cellular Expression Osupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies, 15,29 fibroblasts and SMCs supported 131-fold and 8.7-fold higher rates of factor Xa generation, respectively, than HUVECs (Table 3). Stimulating HUVECs for 4 hours with 1nM TNF␣ increased factor Xa generation 19.7-fold (Table 3).…”
Section: Fibrin Network Density Correlates With Cellular Expression Osupporting
confidence: 92%
“…As in previous studies, 15,29 thrombin generation on fibroblasts and SMCs demonstrated a significantly shorter lag time, higher rate, shorter time to peak, and increased peak height than on unstimulated HUVECs ( Figure 1A, Table 1). Although the final peak turbidities of all clots were similar, fibroblasts and SMCs supported a significantly faster onset and rate of clot formation than unstimulated HUVECs ( Figure 1B, Table 1).…”
Section: Extravascular Cells Enhance Thrombin Generation and Fibrin Fsupporting
confidence: 84%
“…Both of these matrices generate considerable amounts of thrombin on their surface when subjected to flowing LMWHanticoagulated blood. 35 The strong inhibition of platelet adhesion to PMAstimulated ECM at high shear rates in comparison with unstimulated ECM or collagen implies not only a more important role for GPIIb/IIIa but also a diminished role for other non-RGD-directed receptors that support platelet adhesion to unstimulated ECM and collagen, like GPIa/IIa 3132 and/or VLA-6. 4 The role of another non-RGD-directed receptor, GPIb, in platelet adhesion to PMA-ECM is not diminished.…”
Section: Adhesion To the Ecmmentioning
confidence: 99%
“…HUVEC are useful in this context because they express low basal levels of tissue factor, a potent coagulation initiator (11). Collagen was selected for the module base material in the prototype because HUVEC naturally reside on a type IV collagen membrane, albeit not the same type as that (type I) which is readily available.…”
mentioning
confidence: 99%